REVITALIZING KNOWLEDGE RESOURCE CENTRES IN NIGERIAN UNIVERSITIES FOR ENHANCED DIGITAL LIBRARY SERVICES - Hussaini, Suleiman; Sambo, Suleiman; Kokami, Mohammed Shehu (African Journal of Social and Behavioural Sciences, 2025)
Information Communication Technology has changed the way Knowledge Resource Centres (KRC) operate today. This has led most of the KRC to move from the old way of providing services to users to the modern method due to Information Communication Technology which gave birth to digital services. This article aimed to reposition the Information Resource Centre for the effective dissemination of information through digital services. The need to reconfigure the KRC for an effective digital library was also explored. It highlights the concept of a digital library by studying the basic requirements and equipment needed to restore KRC for effective digital services. The article examines some of the opportunities and issues associated with creating a KRC digital library, such as better accessibility, faster information retrieval, copyright/license, and power outages, to name a few. It concluded that KRC, which relies heavily on print resources, should rethink and incorporate digital services to effectively serve its remote users and also figure out how to maintain digital services so that library services are effective. Some recommendations were made which included that KRC should try to persuade and obtain a copyright license from publishers/authors. This would help them provide a better service to their users. KRC should continue to improve users' digital services by ensuring that users can access resources anytime, anywhere, and any day, it will help them change their way of thinking to take advantage of the latest digital technologies/services.